Thromboelastometry Identified Alteration of Clot Stabilization and Factor XIII Supplementation Need in a Patient with Decompensated Liver Disease Undergoing Liver Biopsy - Tomaz Crochemore; Felicio Aragão Savioli (Case Reports in Gastrointestinal Medicine)
Liver disease has been considered the prototype of hemorrhagic disease. Disorder in any component of coagulation system can lead to hemorrhage. Deficiency of factor XIII may impair clot strength and clot stabilization and can be accessed by thromboelastometry. We report a case of a patient with a rapid evolution of liver disease who underwent a liver biopsy. Thromboelastometry was performed, evidencing impairment of clot stability. This clotting disorder was corrected with factor XIII concentrate after unsuccessful administration of antifibrinolytic drugs and hepatic biopsy was performed without hemorrhagic complications. Case Presentation. We report the case of a previously healthy 38-year-old man, who presented to our emergency department with clinical signs of rapid progression of acute liver failure. The laboratory tests revealed platelets of 142x103/mm3, plasma fibrinogen concentration of 221 mg/dl, increased international nationalized ratio (INR 1.9), total bilirubin of 3.9mg/dl, direct bilirubin of 2.3mg/dl, ALT 751U/l, and AST 540U/l without acute bleeding. A liver biopsy was indicated. Based on the results of the thromboelastometry, Tranexamic Acid was administered to correct hyperfibrinolysis followed by factor XIII concentrate to correct factor XIII deficiency. Thromboelastometry was normal despite conventional coagulation tests were still altered. So, liver biopsy was performed with no signs of bleeding and without need of further transfusion. Conclusion. Thromboelastometry may be considered a useful, feasible, and safe tool to monitor and manage coagulopathy in patients with liver disease, with the potential advantage of helping avoid unnecessary transfusion in such patients.